Computer Networks and Distributed Systems International Symposium, CNDS 2013, Tehran, Iran, December 25-26, 2013, Revised Selected Papers - Jahangir, Amir Hossein; Movaghar, Ali; Asadi, Hossein (Communications in Computer and Information Science, 2014)
This book constitutes the refereed proceedings of the International Symposium on Computer Networks and Distributed Systems, CNDS 2013, held in Tehran, Iran, in December 2013. The 14 full papers presented were carefully reviewed and selected from numerous submissions. They are organized in topical sections such as cognitive and multimedia networks; wireless sensor networks; security; clouds and grids.